Conceptual Developments in Environmental Law: An Interdisciplinary Approach - Santoso, Joyo; Selara, Gabriella; Hermanto, Dilly; Tharsyah, Zouvry Imam (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This study examines conceptual developments in environmental law through an interdisciplinary approach to address Indonesia’s increasingly complex ecological and social challenges. It highlights the limitations of traditional normative and legalistic legal frameworks and emphasizes the significance of legal pluralism, ecological justice, and the integration of local knowledge systems. The primary objective of this research is to formulate a holistic conceptual framework that combines ecological sustainability, legal adaptability, and interdisciplinary insights to strengthen environmental governance. This study employs normative legal research supported by secondary data analysis, including statutory regulations, academic literature, and international legal documents. An interpretative and descriptive analytical method is used to synthesize perspectives from legal doctrine, environmental science, philosophy, and sociology in order to develop an innovative and responsive legal paradigm capable of addressing contemporary environmental complexities. The findings reveal that environmental law in Indonesia remains largely dominated by a fragmented and normative approach, which limits the effectiveness of environmental protection. Integrating interdisciplinary perspectives and recognizing local and customary legal systems can promote more inclusive, participatory, and sustainable environmental governance.